Calcium silicate formation using of Nano-silica and wood flour calcareous-treated and investigating of properties of the wood plastic composite obtained from it - Saeid Esmaeiliymoghadam (Regional Information Center for Science and Technology (RICeST), 2016)
This study with aim of evaluation the Nano-silica and wood flour calcareous-treated and evaluation of properties of the wood plastic Nano composite obtained from it performed. For this purpose beginning, wood flour was treated by calcium hydroxide and then with weight ratio of 60 to 40 by Polypropylene with 4 per hundred compound (phc) MAPP compatibilizer in extruder machine were mixed. Beside, Nano silica with weight ratio of 0, 1, 3 and 5 phc was used. Wood plastic Nano composites were fabricated by injection molding technique. Fourier transform infrared spectroscopy was used from wood flour changes after chemical treatment and for morphological study of Nano composites from scanning electron microscopy and X-ray diffraction were used. Mechanical testes include bending (ASTM D790) and tensile (ASTM D638) and physical testes include water absorption and thickness swelling (ASTM D7031-11) on the samples was done. Results showed that by calcium hydroxide treatment, bending and tensile resistance were decreased but bending and tensile modulus were increased. Also with increasing the Nano silica up to specific range, the mechanical properties were improvement. Increase of Nano silica in untreated samples caused increasing of water absorption and in treated samples caused decreasing of water absorption. With increasing of Nano silica, thickness swelling in the samples was decrease. The results of infrared spectroscopy showed that after lime treatment No change has occurred in the absorption band related to the hydroxyl groups. Results of scanning electron microscopy showed that the needle-shaped crystals of calcium hydroxide formed calcium silicate crystals after addition the Nano silica too. As well as results of X-ray diffraction, confirmed calcium silicate crystals.